2001
DOI: 10.1080/0028825x.2001.9512724
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin pigmentation in the adventitious roots ofMetrosideros excelsa(Myrtaceae)

Abstract: Anthocyanin pigmentation is a prominent feature in the adventitious roots Of Metrosideros excelsa. We describe the histological distributions and chemical nature of anthocyanins in these roots, and quantify their antioxidant activity. Anthocyanins were present in one or more cell layers of the root cap, epidermis, hypodermis, and cortex. A narrow band immediately behind the root apex was usually anthocyanin free. Photosensitivity of anthocyanin biosynthesis was evident both for adventitious roots and for plagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Light exposure may partially control the production of these pigments; consequently, they are more abundant in the outer-most layers, where they may protect against UV-B radiation. However, the function of anthocyanins in adventitious roots is still relatively unknown (Solangaarachchi & Gould 2001).…”
Section: Chemistrymentioning
confidence: 99%
“…Light exposure may partially control the production of these pigments; consequently, they are more abundant in the outer-most layers, where they may protect against UV-B radiation. However, the function of anthocyanins in adventitious roots is still relatively unknown (Solangaarachchi & Gould 2001).…”
Section: Chemistrymentioning
confidence: 99%
“…In the cultures of Gynura bicolor treated with JA-Me, the composition of anthocyanins in roots was the same as in the leaves of intact plants (Shimizu et al, 2010). In the roots of Metrosideros excelsa exposed to light cyanidin and delphinidin were found (Solangaarachchi and Gould, 2001). Cyanidin was also identified in the roots of Impatiens (Thakur and Nozzolillo, 1978) and the presence of cyanidin and pelargonidin was recorded in the roots of Raphanus sativus (Harborne, 1963;Ishikura and Hayashi, 1962).…”
Section: Discussionmentioning
confidence: 78%
“…Accumulation of anthocyanin in roots exposed to daylight has been observed in Salix and Zea (Tselas et al, 1979), Fragaria × ananasa (Nemec, 1973), Impatiens spp. (Thakur and Nozzolillo, 1978) and in Metrosideros excelsa (Solangaarachchi and Gould, 2001). Shimizu et al (2010) reported that light irradiation was essential for anthocyanin accumulation induced by JA-Me treatment in Gynura bicolor cultured roots.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, delphinidin-and cyanidin-glycosides were detected in the epidermal, hypodermal, and superficial cortical layers of the adventitious roots of M. excelsa [4]. Additional C-methyl flavonoids from M. excelsa were reported in 2005; these metabolites also lacked oxygenation on the B-ring, and the authors proposed that the combination of these two structural features could be used as taxonomic markers in Metrosideros species [5].…”
mentioning
confidence: 99%